Design, construction and evaluation of a low cost tray dryer (2005)
A low cost food processing tray dryer was designed and constructed using locally available material. The dryer design temperature was such that various types of solid food material can be dried. The maximum temperature specified was 80°C. For better design and operational performance, a survey and design appreciation exercises were carried out on the available tray dryers in the Faculty of Technology, University of Ibadan, and Ibadan. The performance of the dryer was tested using (Dioscorea genus) slices at different thickness and various temperatures and it was found that at higher temperatures and smaller thicknesses the product being dried lose their moisture content at a faster rate. The dryer was able to dry the sample product weighing approximately 24g initially to 8.86g at different time for different temperature as outlined below. For 70°C it dried at 19.5hr, for 60°C it dried at 32hr, and for 50°C it dried at 38hr In order to show the effect of temperature, thickness of product to be dried and velocity a computer program was written using visual basic (software) to simulate the performance characteristics.